Rare Case of Ruptured Sinus of Valsalva: Ruptured Into Left Ventricular Cavity - Taimur, SDM; Khan, SR; Karim, MR; Rahman, MH (Cardiovascular Journal, 2012)
Rupture sinus of Valsalva is a relatively rare condition. We report a rare case of ruptured left sinus of valsalva with aneurysm, presenting with acute left ventricular failure. Transthoracic echocardiography showed an aneurysmal dilatation of the base of interventricular septum and part of the aortic root and a marked turbulent flow from the aortic root to the left ventricle with a continuous systolodiastolic shunting. The patient underwent successful repair of ruptured sinus of valsulva with closure of fistula. During Ventriculotomy the defect was repaired using pledgeted 5/ 0 prolene interrupted sutures and pericardial patch. Key Words: Rupture sinus of valsalva; Aneurysm; Left ventricle DOI: http://dx.doi.org/10.3329/cardio.v4i1.9398 Cardiovasc. J. 2011; 4(1): 96-98